Pemanfaatan Media Sosial Tiktok dengan Menggunakan Affiliate pada Akun @Rosepakpahan Sebagai Sarana Komunikasi Pemasaran - Pakpahan, Roslince; Hardian, Arvin; Ekowati, Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The development of information technology is currently growing rapidly. One of them is characterized by the use of TikTok social media as a means of promotion, purchasing and selling products. The @RosePakpahan account utilizes TikTok by using affiliates for the purpose of earning income or commission from product sales. Marketing communications carried out to promote and sell products are based on the A-I-D-A theory (Attention, Interest, Desire and Action). The method used was an interview with a qualitative approach to Rose Pakpahan. This is to find out how to use TikTok social media by using affiliates on the @RosePakpahan account. The results of this research show that TikTok can make the audience interested in watching content and even buying the products being sold, thus making @RosePakpahan earn economic income. Therefore, TikTok is not only an entertainment medium, but also a product marketing tool.